The Spinning Jenny: A Fresh Look. - Allen, R (Cambridge University Press, 2011)
In “The Industrial Revolution in Miniature,” I calculated that the spinning jenny was profitable to install in England in the 1780s but not in France. My calculations assumed that a spinner using a wheel in a domestic setting worked a total of 100 days per year and spun 100 pounds of coarse cotton (one pound per day). The jenny raised labor productivity to three pounds per day in the “most likely” scenario. I showed that it would have been cheaper to spin 100 pounds per year with a jenny than with a wheel in England, while the reverse would have been true in France. Hence, the jenny was installed in England rather than France. Ugo Gragnolati, Daniele Moschella, and Emanuele Pugliese have pointed out that this argument assumes that output was kept at 100 pounds per year, and the effect of the jenny was to reduce the spinner's work year to only 33–1/3 days per year. They suggest that it was more likely that the spinner would have continued to work 100 days per year and produce 300 pounds of yarn instead. In that case, they argue, it would have been profitable to install the jenny in France as well as England. Profitability would have increased in both countries under these assumptions because capital costs would have been cut by a third if three times as much output was produced from the same capital (although profitability was still much higher in England). Hence, they conclude that economic considerations do not explain the diffusion of the jenny.